Lifestyle and Socioeconomic Transition and Health Consequences of Breast Cancer in the East Asia Region, From 1990 to 2019 - Mubarik, Sumaira; Cao, Jinhong; Wang, Fang; Hussain, Syeda Rija; Liu, Qing; Wang, Suqing; Liu, Yan; Yu, Chuanhua (Frontiers in Nutrition, 2022)
Background Due to its higher prevalence and heterogeneity, female breast cancer (BC) is the widest disease throughout the world. We sought to assess the epidemiological and sociodemographic transitions of BC and to identify the potential risk factors attributed to burden of BC in East Asia. Methods At the regional level of East Asia and at a national level of East Asian countries, we investigated the burden of the incidence of female BC, mortality, and disability-adjusted life years (DALYs) in 2019 and assessed the epidemiological, socioeconomic, and health-linked disparities in incidence of BC and mortality over a 30-year period. The changes in BC’s mortality and DALYs between 1990 and 2019, attributable to varying risk factors, were evaluated in different age groups. Results In 2019, the incidence of and mortality from and DALYs of BC were estimated to be 382,321 (95% UI: 303,308–477,173) incidence cases [age-standardized rate (ASR) of 35.69 per 100,000; 28.32–44.54], 98,162 (79,216–120,112) deaths (ASR of 9.12; 7.36–11.13), and 3,024,987 (2,477, 984–3,659,370) DALYs with an ASR of 282.15 (230.81–341.19) in 2019. It was also observed that out of four most representative locations of East Asia, two (China and Japan) showed more than 60% increase in age-standardized incidence rate between 1990 and 2019. While only Japan females showed a significant rise of 15.3% (95% UI: 2.3–28) in ASR of death and 12.6% (95% UI: 0.5–26.9) in ASR of DALYs between 1990 and 2019. Inclusively, 88 and 81% variations were explained in the incidence of BC and death due to change in sociodemographic index (SDI) in 2019, in East Asia. The highest positive percent changes in death and DALYs between 1990 and 2019 were attributable to high body mass index (BMI), high fasting plasma glucose (FPG), and alcohol consumption in East Asia. Conclusion The burden of death and disability from female BC is the result of multiple risk factors, mainly due to behavioral and metabolic risk factors. The increase of the incidence is related to the westernized lifestyle and diet habits and the improvement of screening and diagnosis techniques in the recent years, whereas the increase in DALYs is mainly attributed to high BMI, high FPG, alcohol use, and high diet in red meat.